2013
DOI: 10.5539/ass.v9n2p53
|View full text |Cite
|
Sign up to set email alerts
|

Attributions to Success and Failure in English Language Learning: A Comparative Study of Urban and Rural Undergraduates in Malaysia

Abstract: This paper presents a descriptive study of Malaysian urban and rural students' attributions for success and failure in learning English as a second language. Data was collected using the Attribution to Success and Failure Questionnaires (ASQ & AFQ), based on previous research conducted by Vispoel and Austin (1995). The findings indicated that urban and rural students held different attribution ratings for the success and failure for learning English as a second language with the urban group being more willing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 57 publications
(27 reference statements)
3
21
1
2
Order By: Relevance
“…For context variable, Thai and Malaysian students scored higher on internal/controllable success outcomes than Japanese students (Gobel et al, 2011). Urban and rural EFL students held different attribution ratings for success and failure with the urban group being more willing to attribute success to their own ability, effort, and study skills than the rural group (Gobel et al, 2013). Lu, Woodcock and Jiang (2014) found no significant differences in attribution patterns between students who learnt through autonomous learning and those who learnt through teacher-centred approach.…”
Section: Review Of the Literaturementioning
confidence: 88%
“…For context variable, Thai and Malaysian students scored higher on internal/controllable success outcomes than Japanese students (Gobel et al, 2011). Urban and rural EFL students held different attribution ratings for success and failure with the urban group being more willing to attribute success to their own ability, effort, and study skills than the rural group (Gobel et al, 2013). Lu, Woodcock and Jiang (2014) found no significant differences in attribution patterns between students who learnt through autonomous learning and those who learnt through teacher-centred approach.…”
Section: Review Of the Literaturementioning
confidence: 88%
“…Dobel and colleagues (Gobel et al, 2013) showed students from urban places score better than their rural counterparts in different language courses. Our present data may confirm their hypothesis as well as conclusions of Fikree and March (Fikree & Marsh, 1996) or Shekhar and Devi (Shekhar & Devi, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…The findings from all instruments indicated their internal attributions towards their success and failure. Gobel, Thang, Sidhu, Oon & Chan (2013) suggest that they are autonomous if students make internal attributions such as strategy, effort and ability. In this sense, they looked like to have learner autonomy.…”
Section: Focus On Elt Journal (Felt)mentioning
confidence: 99%